2014
DOI: 10.1088/0964-1726/23/6/065006
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/fly ash geopolymeric composites as self-sensing structural materials

Abstract: The reduction of graphene oxide during the processing of fly ash-based geopolymers offers a completely new way of developing low-cost multifunctional materials with significantly improved mechanical and electrical properties for civil engineering applications such as bridges, buildings and roads. In this paper, we present for the first time the self-sensing capabilities of fly ash-based geopolymeric composites containing in situ reduced graphene oxide (rGO). Geopolymeric composites with rGO concentrations of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Moreover, extensive research endeavors demonstrated the potential of various nano carbon materials including carbon nanotubes, carbon nanofibres, and nano carbon black for enhancing/modifying cementitious materials [5][6][7][8][9][10]. However, at present the research on nanographite platelets (NGPs) modified cementitious composites just starts [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extensive research endeavors demonstrated the potential of various nano carbon materials including carbon nanotubes, carbon nanofibres, and nano carbon black for enhancing/modifying cementitious materials [5][6][7][8][9][10]. However, at present the research on nanographite platelets (NGPs) modified cementitious composites just starts [1,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the incorporation of rGO in geopolymer composites showed that rGO particles enhance the flexural strength, Young's modulus and toughness of the geopolymeric composites because they display a 2-dimensional structure and strong chemical bonding with the matrix. Further, the addition of low amounts of rGO sheets into geopolymers improved the mechanical properties and reduced the overall porosity of the composite specimens [29,30]. To achieve this potential material enhancement, the development of an efficient and capable method for the mass production of graphene for industrial applications has attracted increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers are synthesized under aqueous alkaline conditions, which are very suitable for dispersing and partially reducing GO . Saafi et al prepared rGO/fly ash geopolymeric composites with improved electrical and piezoresistive properties through in situ reduction of GO in NaOH solutions. The alkaline solution reduced the main functional groups of GO during processing.…”
Section: Introductionmentioning
confidence: 99%